The Academic Effects of VAK Learning Styles on EFL (English as a Foreign Language) Students to learn English Vocabulary - Parween Shawkat Kawther (Zanco Journal of Humanity Sciences)
The main purposes of the study are to investigate about how the linguistic levels of the students and their attitudes towards English language learning process influence their vocabulary learning styles through the practice of visual, auditory or kinesthetic (VAK) learning styles and to find out if the preferred VAK learning styles affect the students’ abilities to increase the amount of the new vocabulary. Also the researcher aims to find out if the gender affects the selection of the VAK learning styles for learning vocabulary and exploring the correlation between EFL instruction and the preferred vocabulary learning styles so as to come up with teaching techniques that can support the quality of teaching and learning English as a foreign language. In particular the study tries to answer the following questions: